Impact of Wheatgrass (Triticum aestivum L.) Supplementation on Atherogenic Lipoproteins and Menopausal Symptoms in Hyperlipidemic South Asian Women – A Randomized Controlled Study. (3rd September 2017) - Kumar, Nitya; Iyer, Uma
ABSTRACT: Objective : The purpose of this study was to evaluate the effect of wheatgrass ( Triticum aestivum L.) on atherogenic lipoproteins, inflammation, and menopausal symptoms. Methods : Fifty-nine hyperlipidemic women were randomized into control ( n = 30) and intervention groups ( n = 29). Intervention group was administered 3.5 g of freeze-dried wheatgrass powder in encapsulated form daily for 10 weeks, while the control group received no intervention. Results : The intervention group experienced a reduction of 5.4% in total cholesterol (TC), 4.4% in low-density lipoprotein cholesterol, and 9.5% in triacylglycerols (TAG); however, high-density lipoprotein (HDL) also reduced by 6% following 10 weeks of intervention. Compared with the control group, the baseline-adjusted post-intervention levels of TC, TAG, and Apolipoprotein B (Apo B) were significantly lower in the experimental group compared with the control group ( p = 0.043, 0.045, and 0.016, respectively). Prevalence of menopausal symptoms saw nonsignificant reductions: vasomotor, 42%; somatic, 33%; and psychological, 50%, while urogenital symptoms remained unaltered. Conclusions : Wheatgrass supplementation at a dose of 3.5 g per day for a period of 10 weeks results in significant reductions in Apo B fraction, TC, and TAG without significantly reducing the HDL cholesterol.